Analysis of Euler-Bernoulli Beams with Arbitrary Boundary Conditions on Winkler Foundation Using a B-Spline Collocation Method - GHANNADIASL, Amin; GOLMOGANY, Mohsen Zare (Engineering Transactions, 2017)
Structural beams are important parts of engineering projects. The structural analysis of beams is required to ensure that they provide the specifics needed to prevent and withstand failure. Therefore, the numerical solution to analyze an Euler-Bernoulli beam with arbitrary boundary conditions using sextic B-spline method is presented in this paper. A direct modeling technique is applied for modeling the Euler-Bernoulli beam with arbitrary boundary conditions on an elastic Winkler foundation. For this purpose, the effect of the translational along with rotational support, the type of beam supports and the elastic coefficient of Winkler foundation are assessed. Finally, some numerical examples are shown to present the efficiency of the sextic B-spline collocation method. To validate the analysis of the Euler-Bernoulli beam with the presented method, the results of B-spline collocation method are compared with the results of the analytical method and the integrated finite element analysis of structures (SAP2000).